2014
DOI: 10.1111/mec.13000
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of gene regulation reveals new insights into the molecular basis of upper thermal limits

Abstract: The cellular stress response has long been the primary model for studying the molecular basis of thermal adaptation, yet the link between gene expression, RNA metabolism and physiological responses to thermal stress remains largely unexplored. We address this by comparing the transcriptional and physiological responses of three geographically distinct populations of Drosophila melanogaster from eastern Australia in response to, and recovery from, a severe heat stress with and without a prestress hardening trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 69 publications
(103 reference statements)
1
21
0
Order By: Relevance
“…Recent work in a variety of taxa provides evidence for substantial heritable variation in patterns of gene expression (Telonis‐Scott et al . ; Leder et al . ), so it is not surprising that transcriptional plasticity can respond to selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work in a variety of taxa provides evidence for substantial heritable variation in patterns of gene expression (Telonis‐Scott et al . ; Leder et al . ), so it is not surprising that transcriptional plasticity can respond to selection.…”
Section: Discussionmentioning
confidence: 99%
“…Observed reductions in the phenotypic plasticity of heat tolerance in selected lines were mirrored by reductions in transcriptional plasticity. Recent work in a variety of taxa provides evidence for substantial heritable variation in patterns of gene expression (Telonis-Scott et al 2014;Leder et al 2015), so it is not surprising that transcriptional plasticity can respond to selection. Recent work in Arabidopsis has also demonstrated that genes with genetically variable expression responses to environmental stress play an important role in adaptation to local environments (Lasky et al 2014), providing an important link between the evolution of transcriptional plasticity and adaptation to abiotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the temperature chosen to harden the flies (37 °C) may influence our capacity to detect significant hardening responses. 37 °C was chosen as this temperature induces a significant hardening response in D. melanogaster (Telonis‐Scott et al ., ), although 34 and 35 °C did not induce a hardening response in the more thermally sensitive D. birchii and D. sulfurigaster (Mitchell et al ., ). Although 37 °C is higher than temperatures commonly experienced in tropical environments (frequently observed maximum temperature ~35 °C, http://www.bom.gov.au), this is not outside the realm of future climate change projections which predict an increase in temperature in the Australian tropics of 1–2 °C by 2030, under an intermediate emissions scenario (RCP4.5) (http://www.climatechangeinaustralia.gov.au).…”
Section: Methodsmentioning
confidence: 99%
“…Shorter exposures (minutes-hours) at more stressful temperatures are often referred to as hardening. Hardening responses in heat resistance have been extensively studied in Drosophila and are linked to the transient upregulation of heat-shock proteins (Telonis-Scott et al, 2014;Willot et al, 2017). In ectothermic species, temperature acclimation (both developmental and adult) and adult hardening treatments increase heat resistance with increasing temperature (Chown, 2001;Hoffmann et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term acclimation may provide the additional time needed to enhance both the physiological and transcriptional milieu further for a larger-magnitude acclimation response than seen with short-term acclimation. Splicing has been shown to be up-regulated in response to artificial selection on cold-tolerance traits (50), and alternatively spliced isoforms of a thermally responsive gene (stv) have been associated with a protective response after multiple heat exposures (51).…”
Section: Rch At 25mentioning
confidence: 99%